1997
DOI: 10.1161/01.cir.96.3.856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Calcium Antagonist Felodipine as Supplementary Vasodilator Therapy in Patients With Chronic Heart Failure Treated With Enalapril

Abstract: Felodipine exerts a well-tolerated additional sustained vasodilator effect in patients with heart failure treated with enalapril, but the only possible long-term benefit was a trend for better exercise tolerance and less depression of quality of life in the second year of treatment. The drug appears to be safe but not clearly efficacious in patients with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
2
30

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 318 publications
(135 citation statements)
references
References 27 publications
1
102
2
30
Order By: Relevance
“…5 In V-HeFT III, felodipine produced a modest reduction in atrial natriuretic peptide levels compared with placebo. 9 In the RESOLVD Pilot trial, candesartan combined with enalapril therapy caused a sustained reduction of BNP of Ϸ30 pg/mL over a period of 43 weeks. 7 None of those trials, however, had an adequate size to examine the response to therapy in subgroups of the population.…”
mentioning
confidence: 99%
“…5 In V-HeFT III, felodipine produced a modest reduction in atrial natriuretic peptide levels compared with placebo. 9 In the RESOLVD Pilot trial, candesartan combined with enalapril therapy caused a sustained reduction of BNP of Ϸ30 pg/mL over a period of 43 weeks. 7 None of those trials, however, had an adequate size to examine the response to therapy in subgroups of the population.…”
mentioning
confidence: 99%
“…Amlodipine and to a lesser extent Felodipine have been shown to be safe in HFrEF. [8,9] If an alternative is needed hydralazine can be added (but should not be used without the ACEi and beta blockers of the earlier steps). [10] Importantly advice is given in which drugs should never be used in the setting of HF (despite being in hypertension guidelines).…”
Section: The Steps To Good Bp Control In Heart Failurementioning
confidence: 99%
“…From 1996 on, other studies [30][31][32][33] , reported the effects of calcium antagonists on morbidity and mortality ratios of congestive heart failure patients who were out of the set of acute myocardial infarction. None of these studies presented evidence significant enough to lead to a modification of the presently employed therapeutic conduct in cases of dilated cardiomyopathy.…”
Section: Studies Of Intermediate Duration With Observations On Ergomementioning
confidence: 99%